Effectiveness of current adhesive systems when bonding to CAD/CAM indirect resin materials: A review of 32 publications - Atsushi Mine; Tomoshige Kabetani; Asuka Kawaguchi-Uemura; Mami Higashi; Yuko Tajiri; Ryosuke Hagino; Dai Imai; Masahiro Yumitate; Shintaro Ban; Mariko Matsumoto; Hirofumi Yatani (Elsevier, 2019)
Summary: The purpose of this review was to assess the available literature regarding bonding between current adhesive systems and computer-aided design/computer-aided manufacturing (CAD/CAM) indirect resin materials, to provide clinicians with a comparative overview of the relevant bonding procedures. An electronic search was performed through PubMed based on the keywords CAD/CAM and dental bonding. Additional relevant literature was obtained from the citations in the articles. A total of 313 papers were identified, of which 281 were excluded as being unsuitable, and an additional 3 papers were identified, giving a total of 32 articles that are included in this review. Based on this survey, it is recommended that microretentive surfaces should be generated by either blasting or hydrofluoric acid etching. This initial process should be followed by silanization to ensure chemical adhesion prior to bonding to CAD/CAM indirect resin composite materials (including Lava Ultimet, KATANA AVENCIA block, Gradia Block, Cerasmart, Paradigm, and Block HC) and CAD/CAM polymer-infiltrated ceramics (such as Vita Enamic). The use of materials containing methyl methacrylate (MMA) also appears to improve the bonding of CAD/CAM poly(methyl methacrylate) (PMMA) resin materials (including XHIPC-CAD/CAM, artBloc Temp, and Telio). Keywords: Adhesive dentistry, Esthetic materials, Dental bonding, Bonding effectiveness, Computer-aided design, Computer-aided manufacturing